Reproduction of Cernuella virgata (Da Costa, 1778) (Gastropoda: Geomitridae) in its natural environment in Southeast Turkey - Ekin, Ihsan (Taylor & Francis Ltd, 2024)
This study aims to investigate the reproductive characteristics of Cernuella virgata (Da Costa, 1778) from Diyarbak & imath;r, Southeast Turkey. From October 2023 to February 2024, the reproductive activities of over 300 individuals were monitored in Yenikoy Cemetery in Diyarbak & imath;r. The snails were first observed mating on 18 October 2023, after the autumn rains, with the first egg laying observed on 3 November 2023. The last mating observation occurred on 8 January 2024. A total of 225 individuals were noticed mating during this period. The number of eggs per clutch ranged from 36 to 114, with an egg hatching time between 18 and 32 days. Eggs were deposited amidst damp mosses, beneath decomposing vegetation, or on the damp soil surface. The spawning period lasts 12-13 weeks. Egg weights varied from 0.60 to 1.20 mg, and egg diameters ranged from 1.10 to 1.42 mm. Hatchling snails had shells with 1.5-2 whorls (protoconch), weighing between 1.15 and 1.72 mg on. The height of the hatchling's shells ranged from 0.75 to 0.94 mm, and the width ranged from 1.21 to 1.38 mm. This study offers a detailed insight into the reproductive biology of C. virgata and marks the first record of the species in the region.
Keywords: Land snail; egg; hatchling; Diyarbak & imath;r